2020
DOI: 10.3390/en13205347
|View full text |Cite
|
Sign up to set email alerts
|

Pigments Production, Growth Kinetics, and Bioenergetic Patterns in Dunaliella tertiolecta (Chlorophyta) in Response to Different Culture Media

Abstract: This work dealt with the study of growth parameters, pigments production, and bioenergetic aspects of the microalga Dunaliella tertiolecta in different culture media. For this purpose, cultures were carried out in Erlenmeyer flasks containing F/2 medium, Bold’s Basal medium, or an alternative medium made up of the same constituents of the Bold’s Basal medium dissolved in natural seawater instead of distilled water. D. tertiolecta reached the highest dry cell concentration (Xmax = 1223 mgDM·L−1), specific growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Furthermore, this pigment has several biotechnological applications for several industries, such as food, feed or pharmaceutical [71][72][73]. In this context, several studies have been conducted in order to optimize microalgae chlorophyll production [22,[74][75][76]. Growth media with lower nitrogen and phosphorus content have been shown to decrease chlorophyll production, while phosphorus-enriched growth media have revealed to be a chlorophyll production promoter [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this pigment has several biotechnological applications for several industries, such as food, feed or pharmaceutical [71][72][73]. In this context, several studies have been conducted in order to optimize microalgae chlorophyll production [22,[74][75][76]. Growth media with lower nitrogen and phosphorus content have been shown to decrease chlorophyll production, while phosphorus-enriched growth media have revealed to be a chlorophyll production promoter [77,78].…”
Section: Discussionmentioning
confidence: 99%
“… Varshney et al (2015) have extensively documented extremophile microalgae strains and their potential for biotechnological applications ( Varshney et al, 2015 ). For instance, species within the Dunaliella genus, notably high-salt-tolerant green marine microalgae, are proficient in producing products of commercial significance, ranging from carotenoids and polysaccharides to proteins, lipids, and vitamins ( Moura et al, 2020 ). Specifically, Dunaliella tertiolecta is renowned for its lipid accumulation, suitable for biofuel production, and its synthesis of carotenoid pigments like β-Carotene, known for antioxidant, anticancer, and anti-inflammatory attributes ( Ebadi et al, 2022 ).…”
Section: Challenges and Future Directions For Engineering Algaementioning
confidence: 99%
“…Interestingly, the biochemical profile of produced biomass using the different operation regimes was not affected regarding the contents of proteins, lipids, and fatty acids. Moura et al [5] investigated Dunaliella tertiolecta growth, pigment production, and bioenergetic parameters in different culture media to select the best cultivation conditions to overproduce such added-value compounds. The authors concluded that the composition of the culture medium has different effects on pigments production, growth kinetics, and energy content, which must be considered for any application of the produced microalgal biomass.…”
Section: Contributions To This Special Issuementioning
confidence: 99%